Investigation on the performances of thrust ball bearing with a novel oil self-transportation biomimetic composite guiding surface - Can Wu; Chen Zheng; Paul D. Teal; Yuan Han; Jing Xu; Xinglin Li (Alexandria Engineering Journal)
Improving the lubrication condition of oil-starved rolling bearings is a proven method to improve their reliability and service life. In this study, a composite surface texture was designed inspired by the microscopic structure of cactus spine, pitcher plant and blood clam. Superhydrophobic surface coating technology was also employed. An oil self-transportation biomimetic composite surface was developed on the guiding surface of a thrust ball bearing. Experimental results show that the biomimetic composite surface effectively drives oil for high-speed directional transport. The biomimetic composite guiding surface bearing demonstrated excellent best vibration and friction torque performance. Compared to conventional bearing, it has an overall vibration performance improvement of 37.4 %, as well as a significant reduction in friction torque of 43.3 % and wear of 72.2 %. We conclude that oil self-transportation biomimetic composite surfaces on rolling bearings can significantly improve the lubrication condition.